Mattering matters in youth suicidality: Implications for implementing in practice - Gordon L. Flett (Child Protection and Practice)
The goal of this paper is to discuss and provide commentary on the construct of mattering in terms of its role in protecting children and adolescents from suicide and its underutilization in violence prevention contexts that target child rights, child health, and child protection. Reviewing and reflecting on decades of psychological research, the current article examines how feelings of mattering among youth are highly protective in terms of suicide risk while feelings of not mattering heighten vulnerability and risk. Mattering is discussed as a source of strength accompanied by hope but it is also a core source of vulnerability when a young person feels unseen, unheard, and unvalued. While mattering is important for all young people, it is especially vital for youth who experience marginalization, including youth in racialized circumstances, youth in foster care, and young people who are members of the LGBTQ ​+ ​community. Research is reviewed that shows consistently that feelings of not mattering are associated with suicide ideation, plans, and attempts. Mattering also has a key role in treatment and the process of recovering from a previous suicide attempt and other adversities. The overarching theme is that mattering is essential in protection and prevention and feelings of mattering can be instilled in young people by caring people in caring settings and communities.